PENGARUH PERMAINAN GOBAK SODOR TERHADAP PENINGKATAN KOMPETENSI SOSIAL ANAK DITINJAU DARI JENIS KELAMIN - Kinanti, Josefine (Persona:Jurnal Psikologi Indonesia, 2017)
Abstract                Social competence is the ability to interact precisely and maintain relationships that have been created, so that it can be received positively by the people around him. Social competence needs to be developed since the individual is still at the age of the children. The purpose of this research is to know the influence of game gobak sodor to increase social competence of children. Subjects of the study were 16 children taken using purposive sampling technique from the study population of 100 students. Criteria of research subjects are children aged 7-8 years and have never played the game sodor gobak. The research data was collected using the children's social competence scale and sociometry. The result of data analysis using Mann Whitney Test obtained significance level of p = 0.001 (p, 0.05), meaning there is significant difference of social competence between experiment group and control group. The Mann Whitney test on the male subject group and the female subject group obtained significance of p = 0.885 (> 0.05), meaning that there is no difference in social competence between boys and girlKeywords: Children's Social Competence, Gobak Sodor, Gender